STUDI PERKEMBANGAN TEKNOLOGI 4G â€“ LTE DAN WIMAX DI INDONESIA - Untsaa Shabrina; Wisnu Broto (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2017)
Long Term Evolution Technology (LTE) is a standard communications network technology in 2010, as the development of GSM (Global System for Mobile Communication) / EDGE (Enhanced Data Rate forÃ‚ GSM Evolution) and UMTS (Universal Mobile Telephone Standard) / HSDPA (High Speed Ã¢â‚¬â€¹Ã¢â‚¬â€¹Downlink Packet Access). WiMAX (Worldwide Interoperability for Microwave Access) is an industry forum that certifies and standardizes products implementing the IEEE 802.16 Wireless MAN standard. This study aims to provide an overview of the development of 4G-LTE and WiMAX technology in Indonesia. The results show that, LTE is able to provide downlink speeds up to 100 Mbps and uplink up to 50 Mbps,Ã‚ while WiMAX is a wireless technology that can overcome various applications with MAN coverage (Metropolitan Area Network), such as backhaul connection, can overcome problems on WiFi backhaul connection, to upgrade Speedy network or Flexi. Keywords: LTE, Wimax, 4G